2023
DOI: 10.3389/fnins.2023.1171549
|View full text |Cite
|
Sign up to set email alerts
|

Triple-network analysis of Alzheimer’s disease based on the energy landscape

Abstract: IntroductionResearch on the brain activity during resting state has found that brain activation is centered around three networks, including the default mode network (DMN), the salient network (SN), and the central executive network (CEN), and switches between multiple modes. As a common disease in the elderly, Alzheimer’s disease (AD) affects the state transitions of functional networks in the resting state.MethodsEnergy landscape, as a new method, can intuitively and quickly grasp the statistical distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…It has been reported that functional organizations of CEN and DMN were impaired in AD ( Joo et al, 2016 ), and functional connectivity between the SN and the other two networks (CEN and DMN) was also altered in AD patients ( He et al, 2014 ). Furthermore, a triple-network (SN, CEN and DMN) analysis of Alzheimer’s disease, focusing on the energy landscape of these networks, revealed that the dynamics of patients with AD tend to be unstable, suggesting fluctuations in network interactions ( Li et al, 2023 ). An increased occupancy rate in State 1 of AD patients possibly suggests a potential brain compensatory mechanism for enhancing cognitive control and coordination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that functional organizations of CEN and DMN were impaired in AD ( Joo et al, 2016 ), and functional connectivity between the SN and the other two networks (CEN and DMN) was also altered in AD patients ( He et al, 2014 ). Furthermore, a triple-network (SN, CEN and DMN) analysis of Alzheimer’s disease, focusing on the energy landscape of these networks, revealed that the dynamics of patients with AD tend to be unstable, suggesting fluctuations in network interactions ( Li et al, 2023 ). An increased occupancy rate in State 1 of AD patients possibly suggests a potential brain compensatory mechanism for enhancing cognitive control and coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Energy landscape analysis has been utilized to analyze abnormalities in brain dynamic dysfunction, including autism spectrum disorder ( Watanabe and Rees, 2017 ), poststroke aphasia ( Fan et al, 2022 ) and AD ( Klepl et al, 2022 ; Li et al, 2023 ). For the AD patient, it was found that the dynamics of AD patients’ EEG were shown to be more constrained - with more local minima, less variation in basin size, and smaller basins ( Klepl et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations